STRUKTUR DAN FUNGSI SOSIAL NYANYIAN RAKYAT SENANDUNG (LULLABY) ENDE BUE-BUE MASYARAKAT DESA SORIMANAON KECAMATAN ANGKOLA MUARA TAIS KABUPATEN TAPANULI SELATAN - Rika Fitrianti; Zulfadhli Zulfahdli (Faculty of Languages and Arts, Universitas Negeri Padang, 2019)
This article contains a discussion of the social structure and function of the song of the humming people (lullaby) Ende Bue-bue. The hum of Ende Bue-bue is a legacy from our ancestors, has noble values that are very useful for the people of the past and modern society. Besides being sung to put the child to sleep, this hum contains a moral value to the singer and listener. Song Ende Bue-bue has a structure like that contained in poetry, namely physical structure and mental structure. Then the social function which is a place for community appreciation, through humming, the community can shed love and hope and prayer of a mother to her child through this humming. There are also social criticisms such as suffering from poverty and betrayal. Hope and prayer and even criticism are wrapped in one hum. The oral tradition of humming, needs to be preserved, considering the values contained in humming are invaluable cultural assets.